2014
DOI: 10.1021/jm501625j
|View full text |Cite
|
Sign up to set email alerts
|

A Conjugate Vaccine Using Enantiopure Hapten Imparts Superior Nicotine-Binding Capacity

Abstract: A leading nicotine conjugate vaccine was only efficacious for one-third of clinical trial participants, likely due in part to its use of racemic nicotine hapten, (±)-3'-AmNic. Immunization of male Wistar rats with (+)-, (-)-, or (±)-3'-AmNicSucTT and subsequent antibody immunoassays suggest that a vaccine using enantiopure (-)-3'-AmNic hapten imparts superior capacity to bind (-)-nicotine. Future nicotine vaccine clinical candidates must incorporate this design consideration (i.e., hapten enantiopurity) in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 43 publications
(54 reference statements)
0
44
1
Order By: Relevance
“…Using Hapten 7 conjugated to CRM 197, an enzymatically inactive and genetically detoxified form of diphtheria toxin (NIC7-CRM), we subsequently demonstrated that hapten load, degree of conjugate aggregation and presence of adducts (small molecules attached to CRM 197 via a covalent bond during the conjugation process) are key antigen attributes that can influence Ab function in mice and non-human primates (NHP) [20]. Others have reported similar findings for some of these characteristics [8], as well as the superiority of using enantiopure hapten over a racemic mixture [26]. Based on these findings, we generated a NIC7-CRM conjugate optimized for hapten load (~16 Hapten7 per CRM 197 molecule), lack of high molecular mass species (~100% monomer), minimal adducts and synthesized with N98% enantiopure hapten.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Using Hapten 7 conjugated to CRM 197, an enzymatically inactive and genetically detoxified form of diphtheria toxin (NIC7-CRM), we subsequently demonstrated that hapten load, degree of conjugate aggregation and presence of adducts (small molecules attached to CRM 197 via a covalent bond during the conjugation process) are key antigen attributes that can influence Ab function in mice and non-human primates (NHP) [20]. Others have reported similar findings for some of these characteristics [8], as well as the superiority of using enantiopure hapten over a racemic mixture [26]. Based on these findings, we generated a NIC7-CRM conjugate optimized for hapten load (~16 Hapten7 per CRM 197 molecule), lack of high molecular mass species (~100% monomer), minimal adducts and synthesized with N98% enantiopure hapten.…”
Section: Introductionmentioning
confidence: 75%
“…(−)-Nicotine was used to prepare Hapten 7, which like the starting material was N98% enantiopure. This is important since it was recently shown in mice that enantiopure nicotine hapten was superior to a racemic mixture, presumably because it optimizes production of antibodies against the naturally occurring isomer [26]. The hapten load (16.1 haptens per CRM 197 molecule) and the molecular size profile (~100% monomer) of NIC7-CRM were measured by reverse-phase high performance liquid chromatography (RP-HPLC) and size exclusion chromatography (SEC) HPLC methods, respectively [20].…”
Section: Nicotine Conjugate Antigensmentioning
confidence: 99%
“…Subgroup analyses have shown that subjects with the highest serum antibody concentrations have double the smoking cessation rates of controls [163,165]. It also appears that nicotine vaccine candidates which incorporate hapten enantiopurity may maximize efficacy compared to use of racemic nicotine hapten [166]. However, a recent study concluded that nicotine vaccines do not appear to improve the chances of stopping smoking when given in addition to varenicline and behavioural support [167].…”
Section: Relative Efficacymentioning
confidence: 99%
“…69 Hapten enantiopurity has been shown to improve quantity and quality of post-vaccination Ab specific for (¡)nicotine, suggesting that enantiopure haptens should be favored over racemic mixtures to generate immunogens for clinical evaluation. 70 Additionally, hapten fluorination, 71 hapten clustering, 72 and conformationally-constrained hapten structures 73 have been explored as potential strategies to design more effective haptens. These data suggest that continuous efforts on hapten synthesis will generate more chemically defined and effective haptens.…”
Section: Pre-clinical Developmentmentioning
confidence: 99%